Molecular dynamics simulations of antimicrobial peptides: From membrane binding to trans-membrane channels - Tieleman, D; Sansom, M (2001)
Using a combination of simulations of alamethicin and other antimicrobial peptides in different environments, we discuss a number of pertinent problems in the biophysics of peptide-lipid interactions and ion channels. Molecular dynamics simulations can be used to obtain detailed information about the structure and dynamics of peptides in membrane environments. Such simulations have yielded interesting information on the dynamics of membrane proteins and of water and ions in ion channels. However, reliably simulating binding to membranes, insertion into membranes, and aggregation of peptides both in and at the surface of membranes remain challenging problems.